Isolation and Molecular Characterization of Novel Chlorpyrifos and 3,5,6-trichloro-2-pyridinol-degrading Bacteria from Sugarcane Farm Soils - Rayu, Smriti; Nielsen, Uffe N.; Nazaries, Loïc; Singh, Brajesh K. (Frontiers in Microbiology, 2017)
Chlorpyrifos is one of the most widely used organophosphate pesticides in agriculture worldwide, but its extensive use has led to the contamination of various soil and water systems. Microbial bioremediation is considered to be one of the most viable options for the removal of chlorpyrifos from the environment; however, little is known about the soil bacterial diversity that degrade chlorpyrifos. Sequential soil and liquid culture enrichments enabled the isolation of bacterial chlorpyrifos degraders with sequence homologies to Xanthomonas sp., Pseudomonas sp. and Rhizobium sp. The efficacy of the three isolated strains: Xanthomonas sp. 4R3-M1, Pseudomonas sp. 4H1-M3 and Rhizobium sp. 4H1-M1 was further investigated for biodegradation of chlorpyrifos and its primary metabolic product, 3,5,6-trichloro-2-pyridinol (TCP). The results indicate that all three bacterial strains almost completely metabolized chlorpyrifos (10 mg/L) and TCP, occurring as a metabolic degradation product, in mineral salt media as a sole source of carbon and nitrogen. The isolated bacterial strains Xanthomonas sp. 4R3-M1 and Pseudomonas sp. 4H1-M3 could also degrade TCP (10 mg/L) as a sole carbon and nitrogen source, when provided externally. Thus, these bacterial strains may be effective in practical application of bioremediation of both chlorpyrifos and TCP.